JOB SATISFACTION IN CRISIS: THE IMPACT OF COVID-19 ON HEALTH PERSONNEL: SATISFACCIÓN LABORAL EN CRISIS: EL IMPACTO DEL COVID-19 EN EL PERSONAL DE SALUD - Itusaca Dueñas, Nora Nicole (2024)
Dear Editor of the Revista de la Facultad de Medicina Humana, Lima, Perú:  I am writing to you regarding the original article titled "Pre-pandemic climate and job satisfaction of nursing staff in an emergency service," published in Volume 23, Issue 02, of the year 2023. In the aforementioned study by Chávez M et al., the significant correlation between the work environment and job satisfaction within the nursing team at Vitarte Hospital is highlighted. However, considering the health emergency situation caused by the COVID-19 virus starting in the year 2020, we believe it is necessary to provide a global perspective on the variation of job satisfaction during this pandemic.